Characterization and modelling of colloidal particles transport in relation to bisphenol a in Bentong River, Malaysia - Mahmood, Albaqqal Zakariya Nafea (2021)
Bisphenol A is considered one of the most prominent endocrine disrupting chemicals worldwide. Upon entering aquatic environments, BPA can adsorb onto solids or colloidal particles which play a significant role in determining its behaviour, distribution and fate due to their unique characteristics, and may inhibit its degradation in water and aid in its transport to distant places posing a severe threat to the ecosystem. This issue was highlighted in Bentong River, which is exposed to sewerage discharge and is a main water supply for the Semantan water intake, a part of the Pahang-Selangor Raw Water Transfer (PSRWT) project that provides millions of people with potable water across the two states, rendering this river a critical importance for public safety. The emphasis was directed toward the possibility of colloidal-bound BPA reaching the water intake downstream of Bentong River. Analytical work consisted of identifying particle size distribution in water while BPA analysis involved isolation from water samples through solid phase extraction followed by analysis using LC-MS/MS. Experimental work involved illustrating the interaction and relationship between BPA and colloidal particles in terms of recovery and competitive sorption. The final step was incorporating the obtained figures and results into an environmental model (WASP) to simulate the fate and transport of colloidal-bound BPA in Bentong River. Results showed that BPA levels in Bentong River varied between 1.13-5.52 ng L-1 in the soluble phase while the highest BPA concentration in the colloidal phase was 2.06 ng L-1. Experimentally, BPA recovery rate declined by 17% with increasing colloidal organic concentration, and BPA’s extraction via SPME was hampered by inhibition interactions with colloidal particles causing an apparent decrease of 16% in recovery rate. Modelling results demonstrated the significance of spatial detail and highlighted the effects of colloidal particles’ concentration and density on BPA’s removal from the water column. All scenarios showed that after 7.5-10 km mark BPA’s concentration started to reach a steady state with very low concentrations which indicated that a downstream transport of colloidal-bound BPA was less likely due to minute BPA levels. The various model scenarios implied that particles with low densities, flowing in aqueous conditions that generate low attachment efficiency milieus and with low colloids, while SPM concentrations have a higher tendency to stay suspended within the water column, and consequently have higher propensity to get transported or relocated to farther distances away from the emission point. Even though a downstream transport of colloidal-bound BPA was less likely due to minute BPA levels as proven in this study, the possibility still exists especially if these levels were to increase later on.